Environment, Urban Unemployment, and Tariffs in the Harris–Todaro Model. Issue 3 (17th July 2013) - Nakamura, Azusa
Abstract: By incorporating the environment into the Harris–Todaro model, this paper examines how introduction of an import tariff on manufactured goods affects urban unemployment and the environment in a less‐developed country. In the Harris–Todaro model, introduction of an import tariff increases urban unemployment when there is no environmental pollution. In contrast, this paper shows that introduction of a tariff may decrease unemployment if the environment is incorporated into the model. Moreover, it is shown that introduction of a tariff improves the environment.